(untitled) (Global Journal of Medical Research, 2017)
The chemotherapy drug doxorubicin (DOX) is well known to induce cardiac and skeletal muscle dysfunction. Previous studies demonstrate that exercise can mitigate dysfunction, reduce myocardial DOX accumulation, and depress markers of oxidative stress, but a putative mechanism is unknown. The aim of this study was to determine whether multidrug resistance protein (MRP) expression contributes to the protective effects of exercise against DOX-induced muscular dysfunction. Lower left ventricle (LV) and soleus DOX concentrations were observed in exercised animals, and MRP-1, MRP-2, and MRP-7 expression was significantly increased in the LV with exercise. No MRP variations were apparent in skeletal muscles following the exercise protocol. As a marker of oxidative stress, malondialdehyde+4 hydroxyalkenal levels were analyzed, and exercise reduced both cardiac and skeletal muscle levels from exercised trained animals treated with DOX had significantly lower levels than SED-DOX. This study suggests increased MRP expression with exercise may contribute to exercise-induced protection in cardiac muscle but not skeletal muscle.